Ankle joint pressure change in varus malalignment of the tibia - Zhu, Yuan (BMC Musculoskelet Disord, 2020)
BACKGROUND: Varus malalignment of the tibia could alter ankle biomechanics, and might lead to degenerative changes of the ankle joint. However, previous studies failed to report the detailed changes of ankle biomechanics in varus malalignment of the tibia. The aim of this biomechanical study was to evaluate how the ankle joint pressure would change in response to the incremental increases in varus malalignment of the tibia. METHODS: Eight fresh-frozen human cadaver legs were tested in this study. Varus malalignment of the tibia and a total of 600 N compressive force was simulated using a custom made fixture. Intra-articular sensors (TeckScan) were inserted in the ankle joint to collect the ankle joint pressure data. The testing sequence was 0°, 2°,4°,6°,8°,10°,12°,14°,16°,18°,20° of tibial varus. RESULTS: As the tibial varus progressed, the center of force (COF) shifted laterally both for the medial and lateral aspect of the ankle joint. For the medial aspect of the ankle joint, the lateral shift reached its maximum at 8° [2.76 (1.62) mm, p = 0.002] of tibial varus, while for the lateral aspect of the ankle joint, the lateral shift reached its maximum at 12° [2.11 (1.19) mm, p = 0.002] of tibial varus. Thereafter, the COF shifted medially as the tibial varus progressed. For the lateral aspect of the ankle joint, The P(mean) increased from 2103.8 (625.1) kPa at 0° to 2295.3 (589.7) kPa at 8° of tibial varus (p = 0.047), significant difference was found between the P(mean) at 0° and 8° (p = 0.047) of tibial varus. Then as the tibial varus progressed, the P(mean) decreased to 1748.9 (467.2) kPa at 20° of tibial varus (p = 0.002). The lateral joint pressure ratio also increased from 0.481 (0.125) at 0° to 0.548 (0.108) at 10° of tibial varus (p = 0.002), then decreased to 0.517 (0.101) at 20° of tibial varus (p = 0.002) . CONCLUSIONS: For mild tibial varus deformities, there was a lateral shift of COF and lateral stress concentration within the ankle joint. However, as the tibial varus progressed, the COF shifted medially and the lateral stress concentration decreased.